2003
DOI: 10.1007/s00247-002-0789-1
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced MR angiography of pulmonary venous abnormalities in children

Abstract: Contrast-enhanced MRA is a powerful, safe, and accurate fast-imaging technique for the anatomical evaluation of pulmonary venous abnormalities. MRA may obviate the need for conventional X-ray angiography. Cardiac catheterization may be reserved for those patients in whom pulmonary vascular resistance needs to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 31 publications
1
24
0
2
Order By: Relevance
“…Contrast-enhanced magnetic resonance angiography (CE-MRA) is a newly developed technique increasing the diagnostic power of cardiac MRI studies and gaining more and more importance in non-invasive cardiac imaging [4,5]. CE-MRA has been proven to be an accurate diagnostic tool for pulmonary and systemic venous anomalies as well as for aortic arch anomalies [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-enhanced magnetic resonance angiography (CE-MRA) is a newly developed technique increasing the diagnostic power of cardiac MRI studies and gaining more and more importance in non-invasive cardiac imaging [4,5]. CE-MRA has been proven to be an accurate diagnostic tool for pulmonary and systemic venous anomalies as well as for aortic arch anomalies [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic MRI has improved its potential in pulmonary thromboembolism, 44 whereas use of multidetector-row CT has been used in quantifying bilateral bronchial narrowing. 45 Separately, magnetic resonance angiography is now the optimal modality to evaluate pulmonary vein stenosis, surpassing the sensitivity of echocardiography 37 and allowing assessment of stenotic lesions in addition to the collateral circulation. A number of other potential clinical applications with respect to the pulmonary vasculature have shown high promise and continue to be the focus of investigation, including the evaluation of patients with chronic thromboembolic disease, 46 arteriovenous malformations, 47,48 and pulmonary vasculitis.…”
Section: Imaging the Pulmonary Circulationmentioning
confidence: 99%
“…Magnetic resonance angiography relies on the intravenous administration of gadolinium to obtain rapid and detailed imaging of lung vascular anatomy with a total imaging time of less than 20 seconds, 37 often acquiring relatively high resolution three-dimensional images within 3 to 4 seconds. This allows for pulmonary vasculature visualization even in significantly dyspneic patients unable to hold their breath for a prolonged period of time.…”
Section: Imaging the Pulmonary Circulationmentioning
confidence: 99%
“…A recent study has shown that MRA of the pulmonary vessels in children is superior to echocardiography [2]. Specifically, MRA may clarify uncertain diagnoses in up to one third of the patient population, and reveal an additional diagnosis in another third.…”
Section: Introductionmentioning
confidence: 98%